Hubungan Perilaku Bullying dengan Kemampuan Interaksi Sosial pada Remaja - Dwi Wahyu Kharismah; Nutrisia Nu’im Haiya; Iwan Ardian (Journal of Health, Medical, and Psychological Studies, 2025)
Adolescence is a period of self-discovery that is vulnerable to environmental influences, including negative behaviors such as bullying. Bullying is an act that can hurt others verbally, physically, or psychologically and has a negative impact on mental health and adolescents' ability to interact socially. Adolescents involved in bullying, either as perpetrators or victims, often experience difficulties in establishing healthy social relationships in school and their surroundings. The purpose of this study was to determine the relationship between bullying behavior and social interaction skills in adolescents. This study was a quantitative study with a cross-sectional approach. The sample consisted of 107 student respondents using total sampling. Data collection was conducted using a questionnaire, which was then analyzed using the Spearman Rank test. The results showed that most respondents were 16 years old, and the majority of respondents engaged in high levels of bullying behavior, namely 90 respondents, and had poor social interaction skills, namely 60 respondents. The Spearman Rank test results showed a value of p = 0.001 (p<0.05). There was a significant relationship between bullying behavior and social interaction skills in adolescents.